2014
DOI: 10.3136/fstr.20.1153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Juicing On Nutrition Qualities of “Sanhua” Plum (Prunus Salicina Lindl.) Juice from 4 Cultivars

Abstract: "Sanhua" plums of 4 cultivars were processed into juice. Pretreatment including heat blanching (HB), microwave blanching (MB) and SO 2 were studied on the inactivation of polyphenoloxidase (PPO), peroxidase (POD) and nutrition qualities. Enzymatic clarification, pasteurization and UHT were also investigated on nutrition qualities. Results showed that PPO and POD could be almost inactivated by HB (95℃

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…The total soluble solids (TSS) content varied between 11.45 and 11.95% in juice samples extracted from fresh red and yellow plums, respectively (Table 2). Values are closed to those obtained by Wang et al (2014), as they found TSS values of plums of 4 cultivars ranged between 10.3 and 12.1%. All treatments applied on red plums in this study enhanced TSS, and this imply the increase in their acceptability to consumers.…”
Section: Physical Propertiescontrasting
confidence: 67%
“…The total soluble solids (TSS) content varied between 11.45 and 11.95% in juice samples extracted from fresh red and yellow plums, respectively (Table 2). Values are closed to those obtained by Wang et al (2014), as they found TSS values of plums of 4 cultivars ranged between 10.3 and 12.1%. All treatments applied on red plums in this study enhanced TSS, and this imply the increase in their acceptability to consumers.…”
Section: Physical Propertiescontrasting
confidence: 67%
“…The evaluation system of juice quality in publications is typically focused on (1) basic physiochemical qualities, which include juice yield, soluble sugar, pH, acidity, color, cloud value, and viscosity; (2) sensory evaluation, which include human-based evaluation of appearance, texture, aroma, and flavors; (3) health qualities and safety concerns, which might include assays of sugar content, vitamin C, antioxidants, phenolics, flavonoids, and microorganisms; and (4) identification of enzymatic activities and by-products [24][25][26][27]. Colloidal stability and enzymatic browning are also part of the evaluation for apple juice and orange juice [28].…”
Section: Introductionmentioning
confidence: 99%